2013
DOI: 10.5858/arpa.2012-0010-oa
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Pathologic Examination of Nonintact, Second-Trimester Fetal Demise Specimens: The Value of Standardization

Abstract: Context.-Management of second-trimester intrauterine fetal demise via dilation and evacuation results in nonintact specimens for pathologic examination. Surgical pathology examination is often mandated; however, evidence on expected findings and specimen evaluation guidelines are lacking.Objective.-To assess pathologic findings of nonintact, second-trimester fetal demise specimens, through comparison of anatomic abnormalities identified on standardized perinatal examination to individualized general pathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, fragmented fetuses are mostly dissected in surgical pathology and finalized by pathologists who do not normally perform fetal autopsy. A study 21 at our institution has shown that in the hands of general surgical pathologists the examination of D&E specimens lacks important findings that are seen by more experienced, trained perinatal pathologists. Because not all institutions can employ a fetal/perinatal pathologist, there is a need for general pathologists to begin to acquire skills necessary to adequately examine tissues from D&E specimens.…”
Section: Standard Of Care For Pathologicmentioning
confidence: 98%
See 2 more Smart Citations
“…However, fragmented fetuses are mostly dissected in surgical pathology and finalized by pathologists who do not normally perform fetal autopsy. A study 21 at our institution has shown that in the hands of general surgical pathologists the examination of D&E specimens lacks important findings that are seen by more experienced, trained perinatal pathologists. Because not all institutions can employ a fetal/perinatal pathologist, there is a need for general pathologists to begin to acquire skills necessary to adequately examine tissues from D&E specimens.…”
Section: Standard Of Care For Pathologicmentioning
confidence: 98%
“…So, it is logical to infer that evaluation of IUFD in D&E specimens, if performed rigorously, should also be useful in evaluating cause of fetal death. Our group 21 has recently performed an institutional retrospective chart review to assess the findings of pathologic examination of disrupted second-trimester fetal demise specimens. 118 specimens were evaluated between May 2006 and October 2010, and the findings of a perinatal pathologist were compared with those examined by general pathologists.…”
Section: 54mentioning
confidence: 99%
See 1 more Smart Citation
“…For active CD during pregnancy, infliximab may be continued up to birth [Van Assche et al 2010]. Infliximab is compatible with breastfeeding since only a small amount is excreted in human milk and is poorly absorbed orally; it thus has low potential to reach detectible levels in the newborn [Ben-Horin et al 2011;Gawron et al 2013].…”
Section: Infliximabmentioning
confidence: 99%
“…[7][8][9][10] As one might expect, this is particularly true if pathologists with expertise in perinatal or pediatric pathology examine the specimens. 11 The aim of our study was to correlate pathology findings with prenatal diagnoses in a large series of D&E procedures done for fetal abnormalities. An important focus was to determine the utility of pathology examination of fragmented specimens to supplement or correct clinical diagnoses in an extensive range of disorders.…”
mentioning
confidence: 99%